2016
DOI: 10.2174/1874321801610010018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endotracheal Intubation Through I-gel and Intubating Laryngeal Mask Airway

Abstract: Background: Supraglottic airway devices (SADs) are very useful airway adjunct in managing anticipated and unanticipated difficult airway and can be used as a ventilating aid and as a conduit for tracheal intubation. The new versions of SADs like i-gel and intubating laryngeal mask airway (ILMA), have advantage of hands-free airway maintenance without the need for tracheal intubation, they can be placed easily without direct visualization of the larynx, ensure predictable ventilation and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Additionally, it is necessary that the success rate of the intubation should be high, intubation should be performed in an acceptable time and complication rate should be low. ILMA suggests a new approach for endotracheal intubation [13]. Shetty et al [14] in their study performed clinical evaluation of endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is necessary that the success rate of the intubation should be high, intubation should be performed in an acceptable time and complication rate should be low. ILMA suggests a new approach for endotracheal intubation [13]. Shetty et al [14] in their study performed clinical evaluation of endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Cases in group 1 had more attempts for SAD insertion than group 2 which was statistically significant (p<0.002). Study by Bharat Choudhary et al, found that success rate for SAD insertion in first attempt was 90% and overall success rate was 100% in both study groups [13] . Dr Juby EV et al, stated that, SAD insertion was successful within 1 st attempt in 93.02% cases of ILMA group and in 95.35% cases in I-GEL group [8] .…”
Section: Discussionmentioning
confidence: 94%
“…In this study there was no statistical significance among demographic parameters, ASA grades in between study groups (Table 1). Study by Bharat Choudhary et al, found that there was no significant difference among demographic parameters [13] . In group 1 of this study, 46.60% cases had ease of insertion score 2, followed by score 3 in 28.30%.…”
Section: Discussionmentioning
confidence: 95%
“…[ 13 ] In contrast, a few authors recorded a higher time for effective ILMA placement which is because of the reason that the rigid broad airway tube of ILMA is slightly difficult to insert and requires additional maneuver for appropriate placement. [ 14 ] Various maneuvers like neck extension, jaw thirst, and lifting maneuvers were employed on the patients who needed second and third attempts, for the device to be successfully placed. Additionally, when ILMA and BlockBuster LMA were compared, it was found that ILMA’s airway tube had an angle of 80° to 85°, but BlockBuster LMA’s airway tube had an angle of >95°.…”
Section: Discussionmentioning
confidence: 99%